2005
DOI: 10.1002/ana.20584
|View full text |Cite
|
Sign up to set email alerts
|

Edema is a precursor to central nervous system peritumoral cyst formation

Abstract: Despite the common occurrence and frequent clinical effects of peritumoral cysts in the central nervous system (CNS), the mechanism underlying their development and evolution is not understood. Because they commonly produce peritumoral cysts and because serial magnetic resonance imaging (MRI) is obtained in von Hippel-Lindau disease patients, hemangioblastomas provide an opportunity to examine the pathophysiology of CNS peritumoral cyst formation. Serial MRI was correlated with the clinical findings in 16 von … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 26 publications
3
98
0
Order By: Relevance
“…As the plasma ultrafiltrate enters the interstitial space of the tumor, interstitial pressure increases and plasma extravasates with convective distribution into the surrounding tissue. If the delivery of plasma from the tumor exceeds the capacity to absorb the extravasated fluid of the surrounding tissue, edema and subsequent cyst formation occur (2). However, this case showed a solid HB with peritumoral edema and aggravated edema at the 5-year follow up.…”
Section: Discussionmentioning
confidence: 69%
“…As the plasma ultrafiltrate enters the interstitial space of the tumor, interstitial pressure increases and plasma extravasates with convective distribution into the surrounding tissue. If the delivery of plasma from the tumor exceeds the capacity to absorb the extravasated fluid of the surrounding tissue, edema and subsequent cyst formation occur (2). However, this case showed a solid HB with peritumoral edema and aggravated edema at the 5-year follow up.…”
Section: Discussionmentioning
confidence: 69%
“…35,36,39 These studies conclude that the mechanisms of formation differ for intratumoral and peritumoral cysts. Whereas intratumoral cyst formation occurs primarily by intratumoral necrosis, peritumoral cysts develop as a result of a tumor interstitial process that begins with generation of edema.…”
Section: Current Studymentioning
confidence: 90%
“…37,66 It has been found that VHL-associated hemangioblastomas are frequently associated with peritumoral edema and/or cysts. 39,40,66 Tumor progression, expanding peritumoral edema, and cyst formation/propagation underlie the clinical signs and symptoms associated with CNS hemangioblastoma. Patients with VHL disease who have CNS hemangioblastomas typically develop symptoms early in life (mean age at presentation 33 years).…”
Section: Cerebellar Hemangioblastomas In Vhl Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Although concomitant hindbrain malformation exists with syringomyelia in the majority of cases (5), terminal syringomyelia in the lower third of the spinal cord is more commonly seen with spinal dysraphism, especially tethered cord (6,7). Syringomyelia also rarely develops in association with primary spinal intramedullary tumors (11,17) or intradural metastases (9). The pathogenesis, natural history and management of terminal syringomyelia remain controversial (18).…”
Section: Introductionmentioning
confidence: 99%